2016
DOI: 10.1038/icb.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Impact of T‐cell‐specific Smad4 deficiency on the development of autoimmune diabetes in NOD mice

Abstract: Type 1 diabetes results from autoimmune-mediated pancreatic beta-cell destruction and transforming growth factor-beta (TGF-β) is known to play a preventive role in type 1 diabetes in non-obese diabetic (NOD) mice. In this study, we investigated the role of Smad4, a key molecule for Smad-dependent TGF-β signaling, in T cells of NOD mice in the pathogenesis of autoimmune diabetes. We generated T-cell-specific Smad4 knockout (Smad4 tKO) NOD mice and assessed the pathological and immunological changes. Smad4 tKO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“… 88 Donghee Kim et al reported that loss of SMAD4 increased the number of activated/memory CD4 + T cell and elevated proliferation potential of effector T cells, and dysregulated T cell activation, which promoted the progress of autoimmune diabetes and the incidence of the disease. 85 These results indicated that SMAD4 in T cells plays critical role in immune response affecting the development of SS in NOD mice.…”
Section: Functions Of Smad4 and Its Mutants In T Cellsmentioning
confidence: 80%
See 2 more Smart Citations
“… 88 Donghee Kim et al reported that loss of SMAD4 increased the number of activated/memory CD4 + T cell and elevated proliferation potential of effector T cells, and dysregulated T cell activation, which promoted the progress of autoimmune diabetes and the incidence of the disease. 85 These results indicated that SMAD4 in T cells plays critical role in immune response affecting the development of SS in NOD mice.…”
Section: Functions Of Smad4 and Its Mutants In T Cellsmentioning
confidence: 80%
“… 87 Kim et al explored the role of SMAD4 in T cells from the nonobese diabetic mice with an autoimmune disease, and found that SMAD4 plays a protective role in the development of autoimmune Sjogren’s syndrome. 85 , 88 These findings suggest that the development of autoimmune diabetes benefits from SMAD4 deletion in T cells.…”
Section: Functions Of Smad4 and Its Mutants In T Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the precise contribution of Dsg-4 to KC differentiation and proliferation remains to be elucidated. Following this line, it has been shown that Smad4, a transcription factor involved in TGF-β-mediated effects such as cell cycling inhibition and immunoregulation, is required for Dsg-4 transcription and, most important, is decreased in PSO ( 38 40 ). Although, in our work, Dsg-4 deficiency did not affect TGF-β mRNA levels, TGF-β/IL-17 ratio may favor inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…These mice exhibited typical features of SS, including increased T cell infiltration into lacrimal glands and increased levels of circulating autoantibodies. In addition, the development of diabetes was also accelerated in these mice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%